2011
DOI: 10.2196/jmir.1523
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Costs of Incentives to Reduce Attrition in Online Trials: Two Randomized Controlled Trials

Abstract: BackgroundAttrition from follow-up is a major methodological challenge in randomized trials. Incentives are known to improve response rates in cross-sectional postal and online surveys, yet few studies have investigated whether they can reduce attrition from follow-up in online trials, which are particularly vulnerable to low follow-up rates.ObjectivesOur objective was to determine the impact of incentives on follow-up rates in an online trial.MethodsTwo randomized controlled trials were embedded in a large on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(142 citation statements)
references
References 26 publications
3
137
2
Order By: Relevance
“…185 An online trial to reduce alcohol consumption found that 3-month retention rates were higher for the group who were offered a £10 gift voucher versus nothing, at a cost of £52 per additional response. 258 Further research in this area might compare this with retention rates and costs for other trial designs to find the method that represents best value for money.…”
Section: Recruitment and Retention Costsmentioning
confidence: 99%
“…185 An online trial to reduce alcohol consumption found that 3-month retention rates were higher for the group who were offered a £10 gift voucher versus nothing, at a cost of £52 per additional response. 258 Further research in this area might compare this with retention rates and costs for other trial designs to find the method that represents best value for money.…”
Section: Recruitment and Retention Costsmentioning
confidence: 99%
“…The larger incentive offered at 12 months appeared to have a positive influence on the response rate (an increase from 36% to 50%), which is in line with studies which tested the effect of larger incentives. 66,89 FEASIBILITY RANDOMISED CONTROLLED TRIAL OF THE MEN'S SAFER SEX WEBSITE NIHR Journals Library www.journalslibrary.nihr.ac.uk…”
Section: Online Outcome Measurementmentioning
confidence: 99%
“…In this study, it is impossible to determine whether intrinsic motivation to take part was affected by the incentive of 50p per additional session, and it would therefore be prudent to run a similar attrition study but without incentives. Money can be a powerful motivator; for example, (Khadjesari et al, 2011) showed found that offering a £10 Amazon voucher to each participant in a longitudinal study resulted in a 9% increased response rate. In our case, it may simply be that money was the most important factor for taking part, and that the similar attrition rates were driven by the identical incentives.…”
Section: Discussionmentioning
confidence: 99%